KONSEP AKHLAK PESERTA DIDIK DALAM KAJIAN ILMU TASAWUF (Analisis Kitab Ar-Risalah Al-Maimuniyah Karya Syaikh Imam Ali bin Maimun) - Nursyamsi, Irfan; Selamet, Selamet; Darifah, Udung Hari (Jurnal Penelitian Pendidikan Islam, 2015)
This study analyzed the concept of morality of students according to the study of Sufism found in the book Ar-Risalah Al-Maimuniyah by Shaykh Imam Ali bin Maimun. The results of the study are as follows: 1) The Book of Al-Risalah Al-Maimuniyah by Shaykh Ali bin Maimun contains about tasawuf studies which basically explain things which include; human nature, human elements, and discussion of the principles of Sufism; 2) Syaik Al-Alim Al-'Arif Billah Ali ibn Maimun in the book Al-Risalah Al-Maimuniyah analogizes the morals of students in 4 subjects, namely: a) الضمة which means that as a student always gather with the teacher; b) الواو which means always following the teacher's instructions and always expecting guidance; c) الالف which means as a student should always follow his teacher so that the creation of the same goal is created; d) النون which means as a student should always remember the services of the teacher who has saved him from the darkness of the world of darkness or ignorance; 3) Implementation in learning can be exemplified by the following: a) Ta'dhim or tawadhu for example by not considering himself smarter than his teacher; b) Polite when speaking; c) Civilized when asking questions.